Analysis and trends of the changes in the graphic interpretation of the quality costs models - Tomov, Mite; Velkoska, Cvetanka (Journal of Production Engineering, 2023)
This paper presents four approaches to the graphic interpretation of the quality costs structure definition models: classical, modern, modified, and visionary approach. These give rise to theoretical graphic quality costs models and illustrate the relationship between the quality costs categories, as well as the relationship between the quality costs categories and the total quality costs and the quality level. The paper comparatively analyzes the underlying assumptions, existing knowledge, and principles characteristic of each approach. This contributes to the shaping of the quality costs categories curves and the overall quality cost curve in the theoretical models. The conducted analysis in the paper will enable forecasting the trend of development of theoretical graphic models and identification of potential stakeholders that contribute to changes in the structure and the behavior of the quality costs categories, and thus the behavior of the overall quality costs.